Binocular temporal visual processing in myopia - Vera-Diaz, Fuensanta A. (J Vis, 2018)
Our ability to utilize binocular visual information depends on the visibility of the retinal images in each eye, which varies with both their spatial and temporal frequency content. Although the effects of spatial information on binocular function have been established, the effects of temporal frequency on binocularity are less well understood. These factors may also vary with refractive error if spatiotemporal sensitivity is affected by structural changes during the emmetropization process that may differentially affect distinct ganglion cells. In a cross-sectional study, we evaluated the potential effects of temporal and spatial frequency on binocularity in young individuals with emmetropia or myopia. Stereopsis and binocular balance were measured as a function of temporal (0–12 Hz) and spatial (1–8 c/deg) frequency. Stereopsis thresholds were measured by determining the minimum disparity at which subjects accurately identified the depth of bandpass-filtered rings. Binocular balance was measured by determining the relative contrast at which subjects reported dichoptic bandpass-filtered letters with equal frequency. Stereopsis thresholds were temporal but not spatial frequency dependent whereas binocular balance was spatial and temporal frequency dependent. There were no differences in monocular spatiotemporal contrast sensitivity between refractive groups in our sample. However, individuals with myopia showed reduced stereopsis with flickering stimuli and greater binocular imbalance at higher spatial and lower temporal frequencies compared to emmetropes. Differences in binocular vision between emmetropia and corrected myopia depend on temporal as well as spatial frequency and may be the cause or consequence of abnormal emmetropization during visual development.